Variation of Female Size and Stage at Maturity in Snow Crab (Chionoecetes Opilio) (Brachyura: Majidae) from the Eastern Bering Sea - Orensanz, Jose Maria; Ernst, Billy; Armstrong, David A. (Journal of Crustacean Biology)
We investigated geographic variation in size and stage (instar) at maturity of snow crab (Chionoecetes opilio) on the eastern Bering Sea shelf. Size-frequency distribution analysis showed that females can reach maturity at four different instars, presumably Instars VIII to XI. Geographic variation in instar structure generates clinal variation in size at maturity, from small size at high latitudes (colder) to large size at low latitudes (warmer). Different pieces of evidence support the hypothesis that geographic variation in mature female size is a phenotypic response to environmental conditions governed by a single reaction norm. Clinal variation conforms to the ‘‘inverse Bergmann’s rule’’. We argue that a single macroecological rule should not be expected to explain all latitudinal size gradients observed in marine invertebrates. Size at maturity fluctuated cyclically, and was negatively and significantly cross-correlated with strength in the recruitment of females to the mature population. Cycles in the latter were manifested as four commensurate and regularly spaced pulses over the last three decades. Mechanisms that may underlay this intriguing phenomenon, including density-dependent growth rate, require further scrutiny. Fil: Orensanz, Jose Maria. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Ernst, Billy. Universidad de Concepción; Chile Fil: Armstrong, David A. University of Washington; Estados Unidos